2010
DOI: 10.1002/art.30080
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genotype on methotrexate polyglutamate variability in juvenile idiopathic arthritis and association with drug response

Abstract: Objective. The response to and toxicity of methotrexate (MTX) are unpredictable in patients with juvenile idiopathic arthritis (JIA). Intracellular polyglutamation of MTX, assessed by measuring concentrations of MTX polyglutamates (MTXGlu), has been demonstrated to be a promising predictor of drug response. Therefore, this study was aimed at investigating the genetic predictors of MTXGlu variability and associations between MTXGlu and drug response in JIA.Methods. The study was designed as a singlecenter cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 24 publications
1
52
1
1
Order By: Relevance
“…3 However, MTX polyglutamates (MTX-PGs) accumulate intracellularly, which are related to clinical response and have been proposed to be of use for therapeutic drug monitoring purposes. [4][5][6][7] In low-dose MTX treatment, the pentaglutamate (MTX-PG5) is the highest order of glutamylation detected, although the triglutamate form (MTX-PG3) of MTX predominates. 5,8 Polyglutamylation retains MTX in the cell because MTX-PGs are a poor substrate for the MTX efflux proteins.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, MTX polyglutamates (MTX-PGs) accumulate intracellularly, which are related to clinical response and have been proposed to be of use for therapeutic drug monitoring purposes. [4][5][6][7] In low-dose MTX treatment, the pentaglutamate (MTX-PG5) is the highest order of glutamylation detected, although the triglutamate form (MTX-PG3) of MTX predominates. 5,8 Polyglutamylation retains MTX in the cell because MTX-PGs are a poor substrate for the MTX efflux proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a longitudinal Dutch cohort of 287 JIA patients on MTX, multivariate analysis corrected for the disease duration prior to therapy, the dose of MTX and the PGA at baseline revealed that SNPs in two transporter genes (ABCB1 SNP rs1045642 or ABCC3 SNP rs4793665) increased the likelihood of achieving an ACR Pedi 70 response within the first year, and the presence of a SNP in SLC19A1 SNP rs1051266 diminished the likelihood two-to three-fold [54]. The membrane transporter SLC19A1 transports MTX into the cell and has been shown to have an effect upon response in RA [55,56]; however, this association was not seen with JIA in prior studies [49,53], and in the current work by de Rotte et al, the association did not remain significant after Bonferroni correction, thus requiring further replication and validation despite a potential physiologic explanation. Although there are variable reports supporting or refuting the association of these SNPs and drug effect in the literature [54], efflux transporters ABCB1 and ABCC3 could affect MTX response by resulting in cellular retention Red dotted lines and squares denote known enzymes inhibited by MTX.…”
Section: Predictors Of Variability/ Individualization Of Therapy: Is mentioning
confidence: 92%
“…Subsequently, the list of MTX target genes has been extended to include aminoimidazole carboxamide ribonucleotide (AICAR) transformylase (gene name ATIC ), which inhibits de novo purine synthesis and promotes the accumulation of AICAR that inhibits AMP deaminase and results in a build up of intracellular AMP, with subsequent increase in extracellular adenosine [43][44][45][46]. Adenosine has Role of methotrexate in juvenile idiopathic arthritis Review been thought to be a large contributor to the site specific anti-inflammatory effects of MTX [45,47,48], and furthermore, pharmacogenomic studies in RA and JIA have provided additional support for the importance of the purine synthesis and adenosine pathways with MTX response [46,49,50]. g-glutamyl hydrolase (GGH), the enzyme responsible for glutamate removal from MTX, transforms MTX into a form that can be effluxed from the cell by the ATP-binding cassette (ABC) family of transporters (Figure 2) [39].…”
Section: Mechanisms Of Action Of Mtxmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of cellular proteins indicative of subclinical disease activity such as calprotectin (MRP 8/14) have been identified as plausible predictors of successful MTX withdrawal [20]. Polyglutamated forms of MTX and folate have been studied for correlation with drug response, and may be useful in the future to predict optimal or poor responders to the drug [21][22][23]. The effect of genotype upon drug response has been extensively studied in adults with RA and recently more in JIA.…”
Section: Non-biologic Dmardsmentioning
confidence: 99%